IMPACT OF POLYCYSTIC OVARY SYNDROME ON WOMEN MENTAL HEALTH AND QUALITY OF LIFE (The Research of Medical Science Review, 2024)
To assess the impact of Polycystic Ovary Syndrome (PCOS) on women's mental health, specifically anxiety and depression, and their quality of life, A cross-sectional study was conducted with 300 women diagnosed with PCOS. Participants were divided by demographic factors such as age, marital status, educational background, employment status, BMI, and family history of PCOS. Mental health was assessed using standardized measures for anxiety and depression, while quality of life was evaluated based on self-reported outcomes. Descriptive statistics, comparisons of symptoms, and multiple linear regression were used to analyze the data., PCOS symptoms significantly affected women's mental health and quality of life. Anxiety and depression levels were highest among women experiencing infertility, weight gain, and hirsutism, with combined symptoms showing the most negative effects on mental health and quality of life. Demographic factors such as age, marital status, education, employment, and BMI were significant predictors of symptom severity. Older women, those unemployed, and those with higher BMI reported more severe symptoms., PCOS has a substantial negative impact on women's mental health and quality of life, with symptoms such as infertility and weight gain contributing most to anxiety, depression, and reduced quality of life. Demographic factors further influence symptom severity, suggesting the need for integrated treatment approaches addressing both physical and psychological health. Future studies should focus on longitudinal research and interventions targeting mental health and socioeconomic challenges faced by women with PCOS.